PGT for structural chromosomal rearrangements in 300 couples reveals specific risk factors but an interchromosomal effect is unlikely - Ogur, Cagri; Kahraman, Semra; Grif, Darren Karl; Yapan, Cigdem Cinar; Tufekci, Mehmet Ali; Cetinkaya, Murat; Temel, Sehime Gulsun; Yilmaz, Alper (ELSEVIER SCI LTD, 2023)
Research question: What factors affect the proportion of chromosomally balanced embryos in structural rearrangement carriers? Is there any evidence for an interchromosomal effect (ICE)? Design: Preimplantation genetic testing outcomes of 300 couples (198 reciprocal, 60 Robertsonian, 31 inversion and 11 complex structural rearrangement carriers) were assessed retrospectively. Blastocysts were analysed either by array-comparative genomic hybridization or next-generation sequencing techniques. ICE was investigated using a matched control group and sophisticated statistical measurement of effect size ('). Results: 300 couples underwent 443 cycles; 1835 embryos were analysed and 23.8% were diagnosed as both normal/balanced and euploid. The overall cumulative clinical pregnancy and live birth rates were 69.5% and 55.8%, respectively. Complex translocations and female age (>= 35) were found to be risk factors associated with lower chance of having a transferable embryo (P < 0.001). Based on analysis of 5237 embryos, the cumulative de-novo aneuploidy rate was lower in carriers compared to controls (45.6% versus 53.4%, P < 0.001) but this was a 'negligible' association (' < 0.1). A further assessment of 117,033 chromosomal pairs revealed a higher individual chromosome error rate in embryos of carriers compared to controls (5.3% versus 4.9%), which was also a 'negligible' association (' < 0.1), despite a P-value of 0.007. Conclusions: These findings suggest that rearrangement type, female age and sex of the carrier have significant impacts on the proportion of transferable embryos. Careful examination of structural rearrangement carriers and controls indicated little or no evidence for an ICE. This study helps to provide a statistical model for investigating ICE and an improved personalized reproductive genetics assessment for structural rearrangement carriers.
Keywords: Interchromosomal effect; Inversion; Next-generation sequencing; Preimplantation genetic testing; Reciprocal translocation; Robertsonian translocation; PREIMPLANTATION GENETIC DIAGNOSIS; IN-SITU HYBRIDIZATION; MEIOTIC SEGREGATION; TRANSLOCATION; CARRIERS; ABNORMALITIES; INFERTILITY; INVERSIONS; SPERMATOZOA; ANEUPLOIDY; Obstetrics & Gynecology; Reproductive Biology